Relapsing optic neuritis and isolated transverse myelitis are the predominant clinical phenotypes for patients with antibodies to myelin oligodendrocyte glycoprotein in India. (October 2016) - Pandit, Lekha; Sato, Douglas Kazutoshi; Mustafa, Sharik; Takahashi, Toshiyuki; D'Cunha, Anitha; Malli, Chaithra; Sudhir, Akshatha; Fujihara, Kazuo
Background: Clinical phenotypes of patients with antibodies to myelin oligodendrocyte glycoprotein (anti-MOG+) are unknown in India. Objectives: Retrospectively to characterise anti-MOG+ patients with inflammatory central nervous system disorders in India. Method: A total of 87 patients with non-multiple sclerosis demyelinating disorders (excluding acute disseminated encephalomyelitis) who were seronegative for anti-aquaporin 4 antibody were retrospectively analysed using a cell-based assay for anti-MOG+ status. Results: Twenty-five patients were anti-MOG+ in this cohort. They represented 28.7% (25/87) of patients who tested negative for anti-AQP4+. Sixty-four per cent (16/25) of anti-MOG+ patients were men and had a relapsing course. Patients with recurrent optic neuritis and those with a single attack of acute longitudinally extensive transverse myelitis were the most common phenotypes. Conclusion: Relapsing optic neuritis was the most common phenotype, contrasting with a lower risk of relapses in transverse myelitis.